2020
DOI: 10.5483/bmbrep.2020.53.9.119
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of pentylenetetrazole-induced seizures in mice with Cereblon gene knockout

Abstract: Epilepsy is a neurological disorder characterized by unpredictable seizures, which are bursts of electrical activity that tempo-rarily affect the brain. Cereblon (CRBN), a DCAFs ( D DB1 and C UL4 a ssociated f actors), is a well-established protein associated with human mental retardation. Being a substrate receptor of the cullin-RING E3 ubiquitin ligase (CRL) 4 complex, CRBN mediates ubiquitination of several substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, there is no evidence to associate CRBN with epilepsy, the anti-inflammatory or anti-ictogenic effects of the drug. In fact, the lack of CRBN in CRBN KO mice does not affect PTZ-induced seizures in these animals [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no evidence to associate CRBN with epilepsy, the anti-inflammatory or anti-ictogenic effects of the drug. In fact, the lack of CRBN in CRBN KO mice does not affect PTZ-induced seizures in these animals [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRBN KO mice have been characterized in multiple phenotypical contexts. A series of studies elucidating the physiological function of CRBN has also been reported in various disease models or under specific challenges [ 15 , 24 , 29 31 ]. The deficiency of CRBN has exhibited protective effects or positive influence under various adverse challenges in vivo .…”
Section: Discussionmentioning
confidence: 99%